Перспективи розвитку інноваційної інфраструктури країни в умовах Індустрії 4.0 - Борисов, І. В. (НДІ ПЗІР НАПрН України, 2022)
У статті розглядається питання перспектив розвитку інноваційної інфраструктури України в умовах цифрової економіки, вирішуються проблеми забезпечення ефективності її функціонування. Проаналізовано чинне законодавство України в цій сфері, міжнародно-правові акти, наукові роботи, зроблені висновки, які мають як теоретичне, так і практичне значення щодо окресленого питання. Зазначено, що інфраструктура (виробнича, соціальна, міська, інноваційна, дослідницька, освітня, інформаційна тощо) в ринковій економіці традиційно розглядається як специфічна система (підсистема) взаємопов’язаних інститутів, цільовою функцією яких є створення загальних умов для функціонування суб’єктів у різних сферах економіки. Зроблено висновок, що інноваційну інфраструктуру України складає сукупність підприємств, організацій, установ, їх об’єднань, асоціацій будь-якої форми власності, які надають послуги із забезпечення інноваційної діяльності (фінансові, консалтингові, маркетингові, інформаційно-комунікативні, юридичні, освітні тощо). Держава повинна забезпечити умови для розвитку інфраструктури розповсюдження знань (патентних організацій, дослідницьких центрів, комунікаційних зв’язків, відкритих баз даних тощо), організувати інноваційну структуру освіти і науки, забезпечивши достатнє фінансування цих систем, а також спрямувати свої зусилля на розвиток творчого потенціалу людини. При цьому вирішення проблеми конкурентоспроможності наукових досліджень та науково-технічних (експериментальних) розробок в сучасних умовах неможливе без інтеграції науково-інноваційної системи України до Європейського дослідницького простору – системи програм та політичних інструментів, що об’єднує інституційне середовище досліджень і розробок держав – учасниць Європейського Союзу та асоційованих членів з метою розвитку міжнародного науково-технічного співробітництва, вільного трансферу знань, мобільності дослідників. Problem setting. In the conditions of the digital economy, the level of development of science and technology is a determining factor in the progress of society and a source of economic growth in Ukraine. Therefore, one of the priority tasks of modern state policy is the formation and ensuring the functioning of a stable innovative infrastructure. Target of research. To conduct an analysis of the current legislation in the field of innovation to identify the effectiveness of the influence of state regulation on the development of innovative infrastructure and its components in the conditions of Industry 4.0. Analysis of recent researches and publications. In the domestic scientific literature, among the representatives of both economic and legal sciences, in the conditions of qualitative changes in the world economy, the problem of the development of innovative infrastructure, its essence and history are dealt with, in particular, by such scientists as H. P. Klimova, I V. Podrez-Ryapolova, A. S. Samorodov, V. V. Maloyvan and others. Article’s main body. The article examines the prospects for the development of Ukraine’s innovative infrastructure in the conditions of the digital economy, and solves the problems of ensuring the effectiveness of its functioning. The current legislation of Ukraine in this area, international legal acts, scientific works have been analyzed, conclusions have been drawn that have both theoretical and practical significance regarding the outlined issue. It is noted that the infrastructure (production, social, urban, innovative, research, educational, information, etc.) in the market economy is traditionally considered as a specific system (subsystem) of interconnected institutions, the purpose of which is to create general conditions for the functioning of subjects in various spheres of economy. It was concluded that the innovative infrastructure of Ukraine consists of a set of enterprises, organizations, institutions, their associations, associations of any form of ownership, which provide services for the provision of innovative activities (financial, consulting, marketing, information and communication, legal, educational, etc.). The state must provide conditions for the development of the infrastructure of knowledge dissemination (patent organizations, research centers, communication links, open databases, etc.), organize an innovative structure of education and science, providing sufficient funding for these systems, and also direct its efforts to the development of human creative potential. At the same time, solving the problem of the competitiveness of scientific research and scientific and technical (experimental) development in modern conditions is impossible without the integration of the scientific and innovative system of Ukraine into the European Research Area – a system of programs and political instruments that unites the institutional environment of research and development of the states that are members of the European Union and associated members for the purpose of development of international scientific and technical cooperation, free transfer of knowledge, mobility of researchers. Conclusions and prospects for the development. Summarizing the above, it should be noted that in the conditions of the digital economy, one of the priority tasks of modern state policy is the formation and ensuring the functioning of a stable innovative infrastructure, in particular, the creation of the necessary organizational, legal and financial conditions for the development of the research infrastructure system, promoting the integration of the scientific and innovative system of Ukraine to the EDP, the development of «digital infrastructures», in particular, e-infrastructures, the accession of Ukraine to the Single Digital Market of the EU, the adaptation of higher education to the European Higher Education Area.
Keywords: інноваційна інфраструктура; е-інфраструктура; дослідницька інфраструктура; індустріальні парки; заклади вищої освіти; innovative infrastructure; e-infrastructure; research infrastructure; industrial parks; institutions of higher education